2020
DOI: 10.1186/s12881-020-01155-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of UGT1A1 (c.-3279 T > G) gene polymorphisms in neonatal hyperbilirubinemia susceptibility

Abstract: Background Neonatal hyperbilirubinemia (NNH) is a common disease in newborns. This research study aimed to assess the associations between uridine diphospho-glucuronate-glucuronosyltransferase 1A1 (UGT1A1, c.-3279 T > G) polymorphisms and NNH risk. Methods We searched PubMed, the Cochrane Library, and the Embase electronic databases. All published eligible studies before July 1, 2019, were searched for this meta-analysis. Results We identified 7 independent studies including 1560 cases. The data showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Other genetic traits not analysed here presumably contributed to increased risk. Other UGT1A1 variants associated to increased risk in Asian population [43] have not been investigated here. Variation in expression of the HMOX gene which encodes for heme oxygenase, the enzyme responsible for transformation of heme into biliverdin, has been shown to be associated with increased risk of NH [38].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Other genetic traits not analysed here presumably contributed to increased risk. Other UGT1A1 variants associated to increased risk in Asian population [43] have not been investigated here. Variation in expression of the HMOX gene which encodes for heme oxygenase, the enzyme responsible for transformation of heme into biliverdin, has been shown to be associated with increased risk of NH [38].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Severe hyperbilirubinemia may cause bilirubin encephalopathy and kernicterus and can result in hearing loss, cerebral palsy and disorders of mental development[ 1 ]. The importance of genetic contributions in neonatal jaundice has been recognized in recent years[ 2 - 5 ]. We previously demonstrated that the genetic polymorphisms of uridine diphosphate glucuronosyltransferase 1A1 ( UGT1A1 ), solute carrier organic anion transporter family member 1B1 ( SLCO1B1 ), SLCO1B3 and glucose-6-phosphate dehydrogenase ( G6PD ) contributed to an increased risk of neonatal hyperbilirubinemia, which reflected the complexity of pathological jaundice[ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for the UGT1A7 gene, rs11692021 polymorphism was related to higher risk of chronic pancreatitis (aOR = 1.76, 95% CI: 1.26–2.46) [ 30 ]. In addition, rs4124874 and rs4148323 polymorphism were associated with in increased risk of hyperbilirubinemia [ 31 , 32 ]. However, rs887829 genotype was related to a decreased risk of hyperbilirubinemia (aOR = 0.55, 95% CI: 0.34–0.89) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%